CTNI-34. PRECISION NEURO-ONCOLOGY - A PILOT ANALYSIS OF PERSONALIZED TREATMENT IN RECURRENT GLIOMA. (14th November 2022) - Lazaridis, Lazaros; Schmidt, Teresa; Oster, Christoph; Blau, Tobias; Pierscianek, Daniela; Siveke, Jens; Bauer, Sebastian; Schildhaus, Hans-Ulrich; Sure, Ulrich; Keyvani, Kathy; Kleinschnitz, Christoph; Stuschke, Martin; et al.
Abstract: PURPOSE: When brain cancer relapses, treatment options are scarce. The use of molecularly matched targeted therapies may provide a feasible and efficacious way to treat individual patients based on the molecular tumor profile. Since little information is available on this strategy in neuro-oncology, we retrospectively analyzed the clinical course of 41 patients who underwent advanced molecular testing at disease relapse. METHODS: We performed Sanger sequencing, targeted next generation sequencing, and immunohistochemistry for analysis of potential targets, including programmed death ligand 1, cyclin D1, phosphorylated mechanistic Target of Rapamycin, telomerase reverse transcriptase promoter mutation, cyclin-dependent kinase inhibitor 2A/B deletion, or BRAF-V600E mutation. In selected patients, whole exome sequencing was conducted. RESULTS: The investigation included 41 patients of which 32 had isocitrate dehydrogenase ( IDH ) wildtype glioblastoma. Molecular analysis revealed actionable targets in 31 of 41 tested patients and 18 patients were treated accordingly (matched therapy group). Twenty-three patients received molecularly unmatched empiric treatment (unmatched therapy group). In both groups, 16 patients were diagnosed with recurrent IDH wildtype glioblastoma. The number of severe adverse events was comparable between the therapy groups. Regarding the IDH wildtype glioblastoma patients, median progression-free survival (mPFS) and median overall survival (mOS) were longer in the matched therapy group (mPFS: 3.8 versus 2.0 months, p = 0.0057; mOS: 13.0 versus 4.3 months, p = 0.0357). CONCLUSIONS: These encouraging data provide a rationale for molecularly matched targeted therapy in glioma patients. For further validation, future study designs need to additionally consider prevalence and persistence of actionable molecular alterations in patient tissue.